Darwin's Theory of Origin of Species (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Commemorative festivities of two major events took place in 2009. To commemorate 400 years since Galileo used the telescope to peer up at the sky, the UN proclaimed it the International Year of Astronomy. Additionally, there were celebrations held all across the world to commemorate the 150th anniversary of the release of Charles Darwin's seminal work, On the Origin of Species. Although the Copernican revolution laid the groundwork for both of these revolutionary events, it took several years for biological sciences to mature and spark a revolution, which accounts for the 250-year gap between them. This has to do with the fact that conservatism, which was defeated in the physical sciences following Galileo, did not lose its hold on biology. This is especially true since biology deals with our comprehension of life, a subject that is more resistant to change than topics pertaining to non-living objects. Galileo made two significant contributions to the field of thought. In order to put heaven and earth on same footing, he first demonstrated the value of experiments and how to get from the specific to the general. The century-old stalemate in biology was here to stay. Even though Leonardo da Vinci's anatomy studies and the first significant event in experimental biology—the British physician William Harvey's demonstration of blood circulation in living bodies in 1628—had given experimental biology a boost, the field's advancement was rather sluggish. The prevailing belief was that you could play with the non-living but not with the living.